Cannabis legislation in Europe : an overview - Observatorio Europeo de las Drogas y las Toxicomanías (Lisboa) (Luxembourg Publications Office of the European Union, 2017)
At a time of increased debate on the laws controlling the use of cannabis in the European Union, this report answers some of the questions most often asked about cannabis legislation. Using a question and answer format, basic definitions and the obligations of countries under international law are set out in a section on 'What is cannabis and what are countries? obligations to control it?' Two following sections examine the links and disparities between the content of the laws and their guidelines on the one hand and the actual implementation of the laws on the other. The final question and answer section considers whether changes in law have affected cannabis use and how much public support for legal change exists, as it looks at the future direction of cannabis legislation in Europe
Disponible también con el mismo contenido en formato electrónico a través de Internet
Keywords: Drogas